2020
DOI: 10.3847/1538-4357/ab7cca
|View full text |Cite
|
Sign up to set email alerts
|

Physical Conditions and Kinematics of the Filamentary Structure in Orion Molecular Cloud 1

Abstract: We have studied the structure and kinematics of the dense molecular gas in the Orion Molecular Cloud 1 (OMC1) region with the N 2 H + 3-2 line. The 6 × 9 (∼ 0.7 × 1.1 pc) region surrounding the Orion KL core has been mapped with the Submillimeter Array (SMA) and the Submillimeter Telescope (SMT). The combined SMA and SMT image having a resolution of ∼ 5.4 (∼ 2300 au) reveals multiple filaments with a typical width of 0.02-0.03 pc. On the basis of the non-LTE analysis using the N 2 H + 3-2 and 1-0 data, the den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
3
8
4
Order By: Relevance
“…i = 0). The mean central density we infer for the OMC-1 portion of the ISF is a factor of three lower than the nominal volume density of 3 × 10 6 cm −3 found by Teng & Hirano (2020) for N 2 H + filamentary structures in OMC-1 (outside of cores) through non-LTE modelling of the N 2 H + (3-2) and (1-0) lines. Our dust continuum estimate of the volume density is, however, affected by a rather large uncertainty of a factor of ∼2-3 or more in the OMC-1 subregion, which is due to particularly uncertain dust opacity and temperature gradient effects in this unusually dense and strongly irradiated area (see e.g.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…i = 0). The mean central density we infer for the OMC-1 portion of the ISF is a factor of three lower than the nominal volume density of 3 × 10 6 cm −3 found by Teng & Hirano (2020) for N 2 H + filamentary structures in OMC-1 (outside of cores) through non-LTE modelling of the N 2 H + (3-2) and (1-0) lines. Our dust continuum estimate of the volume density is, however, affected by a rather large uncertainty of a factor of ∼2-3 or more in the OMC-1 subregion, which is due to particularly uncertain dust opacity and temperature gradient effects in this unusually dense and strongly irradiated area (see e.g.…”
Section: Resultscontrasting
confidence: 73%
“…In any event, a comparison of the N 2 H + map of Hacar et al (2018) with the NH 3 map of Monsch et al (2018) clearly indicates that the abundance of N 2 H + is far from uniform in the OMC-1 region. The most extreme difference between the two maps is that no N 2 H + emission is detected in the immediate vicinity of Orion KL (see also Teng & Hirano 2020), presumably due to the destruction of N 2 H + by CO, while strong NH 3 (1,1) and NH 3 (2,2) emission is seen in the Monsch et al (2018) data and a prominent column density peak is observed in our data (cf. Figs.…”
Section: Comparison Between Artémis and N 2 H +contrasting
confidence: 54%
See 1 more Smart Citation
“…A detailed analysis of the N 2 H + (1-0) hyperfine line opacities and excitation suggest that the density of these fibers reaches values of n(H 2 ) > 10 7 cm −3 (see Hacar et al 2018, for a discussion). This hypothesis is supported by the recent detection of extended N 2 H + (3-2) emission towards the entire OMC-1 region (Teng & Hirano 2020).…”
Section: New Sepia660 Observationsmentioning
confidence: 60%
“…The relatively higher abundances of N 2 H + also makes this molecule a favourable target for observations in comparison with other deuterated isotopologues (e.g., N 2 D + ) and species (e.g., DCO + ). Most studies typically investigate low-frequency transitions of this molecule, such as N 2 H + (1-0) (93 GHz; e.g., Hacar et al 2018) or N 2 H + (3-2) (279 GHz; e.g., Teng & Hirano 2020), limiting the dynamic range of these observations to densities of n(H 2 ) 10 6 cm −3 . However, the observation of high-J transitions (J > 4-3) necessary to confirm the existence of gas at higher densities has been largely hampered by the more challenging access to frequencies above >300 GHz.…”
Section: Initial Gas Conditions In Massive Clustersmentioning
confidence: 99%